Combining the Physical-Chemical Approach with Standard Base Excess to Understand the Compensation of Respiratory Acid-Base Derangements: An Individual Participant Meta-analysis Approach to Data from Multiple Canine and Human Experiments - Zadek, Francesco; Danieli, Andrea; Brusatori, Serena; Giosa, Lorenzo; Krbec, Martin; Antolini, Laura; Fumagalli, Roberto; Langer, Thomas (Anesthesiology, 2024)
BACKGROUND: Several studies explored the interdependence between Paco2 and bicarbonate during respiratory acid-base derangements. The authors aimed to reframe the bicarbonate adaptation to respiratory disorders according to the physical-chemical approach, hypothesizing that (1) bicarbonate concentration during respiratory derangements is associated with strong ion difference; and (2) during acute respiratory disorders, strong ion difference changes are not associated with standard base excess. METHODS: This is an individual participant data meta-analysis from multiple canine and human experiments published up to April 29, 2021. Studies testing the effect of acute or chronic respiratory derangements and reporting the variations of Paco2, bicarbonate, and electrolytes were analyzed. Strong ion difference and standard base excess were calculated. RESULTS: Eleven studies were included. Paco2 ranged between 21 and 142 mmHg, while bicarbonate and strong ion difference ranged between 12.3 and 43.8 mM, and 32.6 and 60.0 mEq/l, respectively. Bicarbonate changes were linearly associated with the strong ion difference variation in acute and chronic respiratory derangement (β-coefficient, 1.2; 95% CI, 1.2 to 1.3; P < 0.001). In the acute setting, sodium variations justified approximately 80% of strong ion difference change, while a similar percentage of chloride variation was responsible for chronic adaptations. In the acute setting, strong ion difference variation was not associated with standard base excess changes (β-coefficient, -0.02; 95% CI, -0.11 to 0.07; P = 0.719), while a positive linear association was present in chronic studies (β-coefficient, 1.04; 95% CI, 0.84 to 1.24; P < 0.001). CONCLUSIONS: The bicarbonate adaptation that follows primary respiratory alterations is associated with variations of strong ion difference. In the acute phase, the variation in strong ion difference is mainly due to sodium variations and is not paralleled by modifications of standard base excess. In the chronic setting, strong ion difference changes are due to chloride variations and are mirrored by standard base excess.
Keywords: acidobazická rovnováha; Chlorides; hydrogenuhličitany; Animals; Dogs; Sodium; koncentrace vodíkových iontů; lidé; Bicarbonates; Acid-Base Equilibrium; chloridy; Hydrogen-Ion Concentration; sodík; Humans; zvířata; psi